VASILY EKZEMPLYARSKY’S IDIOCY AND MODERNITY - Печеранський, І. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article deals with the phenomenon of idiocy in the context of art of Vasil Ekzemplyarsky (1875-1933) a professor of moral theology of the Kiev Theological Academy. Content and the importance of this concept for the restoration of the ideals of social and church and secular "healthy" life in the modern globalized world are defined.